Pragmatic Language in Discussions of Tax Strategy and Corporate Social Responsibility Projects among Management Students - Rahmat Burhamzah; Muftihaturrahmah Burhamzah; A. Reski Almaida Dg Macenning (Universitas Negeri Makassar, 2025)
Abstract. This study aims to examine the use of linguistic pragmatics in the group discussions on tax strategy and Corporate Social Responsibility (CSR) projects among management students. Employing a qualitative research design with a case study approach, data were collected through participant observation, audio-video recordings of group discussions, semi-structured interviews, and document analysis. The data were analyzed using Speech Act Theory (Austin and Searle) and Grice’s theory of implicature to interpret implied meanings and communicative strategies within group interactions. Findings reveal that students employ various speech acts, including directives, assertives, expressives, and commissives, which function not only to convey information but also to establish social roles and influence group dynamics. The use of implicature and presupposition facilitates implicit communication, expediting the discussion process and maintaining group harmony. Mitigation and persuasion strategies proved effective in building consensus and managing conflicts. Social position differences within groups influenced pragmatic language use patterns, where dominant members tended to use more direct language, while others preferred subtler and implicit expressions. This study underscores the significance of pragmatic competence as a pivotal communication skill in both academic and professional contexts. It is recommended that educational institutions integrate pragmatic communication training into curricula to enhance students’ effective communication skillsKeyword: linguistic pragmatics, speech acts, implicature, tax strategy, Corporate Social Responsibility, academic communication